Systemic antitumor effect by regional hyperthermia combined with low-dose chemotherapy and immunologic correlates in an adolescent patient with rhabdomyosarcoma – a case report. (1st January 2020) - Issels, Rolf D.; Lindner, Lars H.; von Bergwelt-Baildon, Michael; Lang, Peter; Rischpler, Christoph; Diem, Heinz; Mosetter, Barbara; Eckl, Judith; Schendel, Dolores J.; Salat, Christoph; Stötzer, Oliver; Burdach, Stefan; et al.
Abstract: Introduction: An abscopal effect is a clinical observation whereby a local treatment is associated with regression of metastatic cancer at a site distant from the primary location of treatment. Here, we describe the clinical systemic effect induced by regional hyperthermia combined with low-dose chemotherapy and provide immunologic correlates. Case presentation: A 15-year-old patient had been diagnosed with alveolar rhabdomyosarcoma (ARMS). All previous treatment options failed in the patient including haploidentical stem cell transplantation and donor lymphocyte infusion. The patient presented with local and metastatic disease, and upon admission, underwent regional hyperthermia combined with low-dose chemotherapy. Immediately following therapy severe skin reactions were observed. Skin biopsies revealed an intraepithelial lymphocytic infiltration dominated by CD3 + /CD8 + T cells with a regular network of dendritic cells. Clinical images compared before and during sequential treatment cycles showed complete metabolic response of the local tumor for more than 10 months of therapy. In addition, metastases completely regressed although they were not direct targets of regional hyperthermia. The systemic effect was associated with enhanced frequency of NK cells and T cells expressing the lectin-like natural-killer group 2 D activating receptor (NKG2D), an increase of the CD56 bright subset of NK cells, as well as an increase of effector/memory and effector CD8 + and CD4 + T cells in the blood while the percentage of CD25 + FOXP3 + regulatory T cells declined. Conclusions: Regional hyperthermia combined with low-dose chemotherapy had the potential to create a systemic effect which was associated with activation of NK cells and T cells.